ORGANOLEPTIC TESTS OF PEMPEK WITH VARIOUS SURIMI FORMULATIONS OF SANGKURIANG CATFISH (Clarias gariepsinus) - Idealistuti Idealistuti; Suyatno Suyatno; Mutatauwi’ah Mutatauwi’ah; Nico Syahputra Sebayang (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2023)
This study aims to study various surimi formulations of Sangkuriang catfish (Clarias gariepsinus) for the resulting pempek, using the experimental method using a Randomized Block Design (RBD) arranged in a non-factorial manner with one treatment of various formulations of surimi Sangkuriang catfish (Clarias gariepsinus) consisting of of six factors and repeated four times. Pempek organoleptic test results with hedonic tests on color, aroma, and taste. The highest preference value for the color of pempek made from sangkuriang catfish surimi in the L1 treatment (0.25 parts of sangkuriang catfish surimi and 1.00 parts of tapioca flour) with a clean white pempek color typical of fish pempek with an average value of 4.30 (criterion panelists liked). The highest preference value for the taste and aroma of pempek made from sangkuriang catfish surimi was found in treatment L6 (1.50 parts of sangkuriang catfish surimi and 1.00 parts of tapioca flour) with a savory taste and dominant pempek aroma with an average value of 3 .90 (panelists preferred criteria) and 4.30 (panelists preferred criteria).